The Fires of faith - Heer, Friedrich, 1916- (New York : Newsweek Books, 1973)
Traces milestones of history from Constantine's unification of the western half of the Roman Empire under his name in 312 to the fall of Constantinople in 1204.
Includes index.
Keywords: Middle Ages; Middle Ages